Kualitas Karya Tulis Ilmiah Mahasiswa: Hubungan Persepsi dan Karakteristik Dosen Pembimbing - Regina Satya Wiraharja; Felicia Kurniawan (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: Since 2006 evaluation of scientific writing process, as graduation requirement in Faculty of Medicine Atma Jaya Catholic University, has not been done. The objective of this study is to find out supervisors perceptions on quality of under graduate theses and its relationship to supervisors’ characteristics.Method: This descriptive study was done to 29 supervisors. Interviews were done using questionnaire. Dependent variable was perceptions on quality of under graduate theses (idea, proposal, writing process, presentation and publication). Independent variables were characteristic, knowledge, attitude and behavior of supervisors related to process of scientific writing. Data was analyzed using chi-square test.Results: There was equal proportion (50% vs 50%) between good perception and bad perception on quality of undergraduate theses. Significant relationship was found between perception on quality with supervisors attitude (p=0.04) and master degree (p=0.02). Supervisors aged 45 years old and less (53% vs 47%), have taught for 10 years and less (64% vs 39%), have academic position as assistant and lectur (5% vs 47%), have published articles within the last 3 years (40% vs 60%), have more than one research within the last 3 years (56% vs 4 %), have non positive attitude (78% vs 27%), supervise students twice or more (57% vs 43%), meet student for less than 45 minutes per meeting (67% vs 33%), were more like to perceive low quality of under graduate theses.Conclusion: Supervisors generally perceive that qualities of under graduate theses are still low. Positive attitude and non-magister supervisors tend to perceive the quality of theses to be good.